Surface Characterization on Electrophoretic Deposition Oof 316l Stainless Steel with Dissolved Chitosan for Biomedical Application - Setyarini, Putu Hadi; Gapsari, Femiana; Harjo, Apollo Ode Rea (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
Of many compounds materials, metallic biomaterial is widely used in human medical devices. An implant material's corrosion resistance impacts its flexibility and longevity. This corrosion resistance is also an important consideration for biocompatibility. This biomaterial contains stainless steel whcih may corrode after being installed in the human body sinceÂ the passivity of stainless steel disappears when it is exposed to acids in the human body for a long duration. In addition, lacks of oxygen inhibits the formation of a new Cr2O3 layer for corrosion protection. Based on this phenomenon, an advance treatment is required to improve the resistance corrosion of implant. This study investigates the effect of the concentration and duration of chitosan on the thickness and corrosion resistance of biomaterials. The concentration of chitosan used was 0.08%, 0.16%, and 0.24% while the voltage used was constant at 10 V. The test results demonstrated the lowest corrosion rate occrured for 0.24 % chitosan concentration with 30 minutes coating duration. The lowest corrosion rate achieved was 0.014 mmpy and the maximum thickness was 75.4 Î¼m. This study could be then used as a new solution to increase the safety of existing implants using biodegradable and non-toxic compounds. The next experiment should be implantation in real human body.